2017
DOI: 10.1002/jat.3497
|View full text |Cite
|
Sign up to set email alerts
|

Endocrine disruption: In silico interactions between phthalate plasticizers and corticosteroid binding globulin

Abstract: Endocrine disruption is a phenomenon when a man-made or natural compound interferes with normal hormone function in human or animal body systems. Endocrine-disrupting compounds (EDCs) have assumed considerable importance as a result of industrial activity, mass production of synthetic chemicals and environmental pollution. Phthalate plasticizers are a group of chemicals used widely and diversely in industry especially in the plastic industry, and many of the phthalate compounds have endocrine-disrupting proper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 62 publications
0
7
0
Order By: Relevance
“…Five GOIs ( 17βHSD14, 17βHSD12, NPC2, PTCH3, SMO ) that have sterol binding pockets were used in silico modelling. In silico modelling has previously demonstrated phthalates and steroids without an aromatic A-ring are capable of binding to sterol-binding proteins ( Sheikh and Beg, 2017 ; Khalturin et al, 2018 ). Patched genes have multiple functionally redundant homologs that cannot discriminate between ligands ( Carpenter et al, 1998 ; Zhulyn et al, 2015 ; Hu and Song, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…Five GOIs ( 17βHSD14, 17βHSD12, NPC2, PTCH3, SMO ) that have sterol binding pockets were used in silico modelling. In silico modelling has previously demonstrated phthalates and steroids without an aromatic A-ring are capable of binding to sterol-binding proteins ( Sheikh and Beg, 2017 ; Khalturin et al, 2018 ). Patched genes have multiple functionally redundant homologs that cannot discriminate between ligands ( Carpenter et al, 1998 ; Zhulyn et al, 2015 ; Hu and Song, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, in view of their wide‐ranging applications along with the leach out propensity, environmental contamination occurs, and both humans and animals are extensively exposed to plasticizers. Recent studies have reported the potential interference of plasticizers with various endocrine pathways resulting in signaling disruption (Sheikh, 2016; Sheikh et al, 2016; Sheikh & Beg, 2017, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…7 The potential mechanisms underlying phthalate toxicity remain unclear but endocrine disruption is a possibility. 8 In particular, exposure to dibutyl phthalate (DBP) has been reported to be associated with reduced levels of testosterone and reduced anogenital distance (AGD) in newborns, a sexually dimorphic landmark indicative of altered fetal androgen levels. 9,10 Perinatal exposure of rats to some phthalates, including DBP, results in a range of reproductive tract defects in male offspring, including reduced AGD, CPT, multinucleated gonocytes, and reduced semen quality.…”
Section: Introductionmentioning
confidence: 99%